Contextual factors matter: A two-year exploration into the impact of contextual factors on elite women`s rugby sevens match-play movement demands (PLOS ONE, 2025)
Introduction and aims Women`s rugby sevens is a rapidly growing sport that imposes unique match-play movement demands on participants. This research investigated the effect of contextual factors on the match-play movement demands of international and domestic women`s rugby sevens players.